Understanding the Mechanisms by Which Epigenetic Modifiers Avert Therapy Resistance in Cancer - Quagliano, Anthony; Gopalakrishnapillai, Anilkumar; Barwe, Sonali P. (Frontiers in Oncology, 2020)
The development of resistance to anti-cancer therapeutics remains one of the core issues preventing the improvement of survival rates in cancer. Therapy resistance can arise in a multitude of ways, including the accumulation of epigenetic alterations in cancer cells. By remodeling DNA methylation patterns or modifying histone proteins during oncogenesis, cancer cells reorient their epigenomic landscapes in order to aggressively resist anti-cancer therapy. To combat these chemoresistant effects, epigenetic modifiers such as DNA hypomethylating agents, histone deacetylase inhibitors, histone demethylase inhibitors, along with others have been used. While these modifiers have achieved moderate success when used either alone or in combination with one another, the most positive outcomes were achieved when they were used in conjunction with conventional anti-cancer therapies. Epigenome modifying drugs have succeeded in sensitizing cancer cells to anti-cancer therapy via a variety of mechanisms: disrupting pro-survival/anti-apoptotic signaling, restoring cell cycle control and preventing DNA damage repair, suppressing immune system evasion, regulating altered metabolism, disengaging pro-survival microenvironmental interactions and increasing protein expression for targeted therapies. In this review, we explore different mechanisms by which epigenetic modifiers induce sensitivity to anti-cancer therapies and encourage the further identification of the specific genes involved with sensitization to facilitate development of clinical trials.